No one is saved alone. Critiques by Teachers and Students of Contemporary Society (Praxis Educativa, 2026)
The aim of this article is to describe the reactions of secondary school teachers and students to discourses thatexalt supposed freedom, individualism, and competition in contemporary society. The central hypothesis we seekto develop is that, within the school setting, individuals critically engage with logics that promoteself-management, survival of the fittest, and meritocracy as regimes of truth (Foucault, 1979), particularly intimes and contexts where inequalities are deepening and intensifying. At the same time, these individualsenvision alternative ways of living together, grounded in the notion that "no one is saved alone," where solidarityand camaraderie become central. To explore this, we designed a multi-method approach that includes audiovisualproductions and in-depth interviews with both teachers and students. The findings reveal that situations ofinsecurity, poverty, economic crisis, death, suffering, cruelty, and selfishness do not prevent individuals in schoolcontexts from empathizing with others and recognizing the need to both support and be supported by oneanother. They highlight the importance of solidarity, empathy, coexistence, and teamwork as fundamental tobuilding a shared life in society
Keywords: criticism; schooling; poverty; neoliberalism; students; teachers